Uji Aktivitas Antibakteri Ekstrak Kasar Bonggol Nanas (Ananas comosus (L.) Merr.) Terhadap Salmonella enterica Serotipe Typhi - Kusumawardhani Fildzah Hani; Syarifah Syarifah; Riri Novita Sunarti (Pandawa Institute, 2022)
Salmonella enterica serotype Typhi is sufficient to cause clinical infection, compared to other serotypes. Antibiotics are often used as antibacterial, but inappropriate use of antibiotics can cause serious side effects. Pineapple hump is an alternative because of its better enzyme activity potential as an antibacterial. This study aimed to determine the effect of the antibacterial activity of the crude extract of pineapple weevil (Ananas comosus (L) Merr) on the growth of Salmonella enterica serotype Typhi. This study is an experimental study (RAL) with 7 treatments and 4 replications. Tested by diffusion method at concentrations of crude pineapple wee extract 50%, 60%, 70%, 80%, 90%, 100% and positive control chloramphenicol 30 g. The results showed that the crude extract of pineapple hump in this study had no effect as an antibacterial on the growth of Salmonella enterica serotype Typhi. However, this activity can still be proven by isolating certain compounds and modifying the method used in pineapple weevil extraction which can produce antibacterial compounds in pineapple weevil to optimize antibacterial activity.